Project-Based Learning Trends in Early Childhood Education: Building Children's Creativity and Independence - Laila Nursafitri (Journal of Gemilang, 2025)
This study aims to describe the implementation of Project-Based Learning (PjBL) in Early Childhood Education (PAUD) and analyze its influence on the development of children's creativity and independence. The method used is descriptive qualitative with data collection techniques in the form of observation, in-depth interviews, and documentation of teachers, students, and parents in several PAUD institutions. The results of the study indicate that the implementation of PjBL can stimulate children's creativity through exploratory activities and the creation of real works relevant to their world. In addition, children show increased independence in completing tasks, making decisions, and being responsible for project results. The role of teachers as facilitators and parental involvement greatly influence the success of PjBL implementation. Despite facing several challenges, such as limited resources and teacher understanding, project-based learning has proven to be an effective and enjoyable approach in building character in early childhood.